2005
DOI: 10.1016/j.jalgebra.2005.03.029
|View full text |Cite
|
Sign up to set email alerts
|

An induction theorem for the unit groups of Burnside rings of 2-groups

Abstract: Let G be a 2-group and B(G)× denote the group of units of the Burnside ring of G. For each subquotient H/K of G, there is a generalized induction map from B(H/K)× to B(G)× defined as the composition of inflation and multiplicative induction maps. We prove that the product of generalized induction maps ∏ B(H/K)× → B(G)× is surjective when the product is taken over the set of all subquotients that are isomorphic to the trivial group or a dihedral 2-group of order 2n with n ≥ 4. As an application, we give an alge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 7 publications
(16 reference statements)
0
25
0
Order By: Relevance
“…They are discussed in Bouc [8,Sections 5,7], Yalçın [18,Section 3], Yoshida [19,Sections 2,3]; see also a review in [3,Section 10]. For the purposes of the present article, though, we need invoke only Yoshida's result [19, 3.5], which asserts that the maps die G commute with the five elemental maps.…”
Section: Constructions and Definitionsmentioning
confidence: 97%
See 2 more Smart Citations
“…They are discussed in Bouc [8,Sections 5,7], Yalçın [18,Section 3], Yoshida [19,Sections 2,3]; see also a review in [3,Section 10]. For the purposes of the present article, though, we need invoke only Yoshida's result [19, 3.5], which asserts that the maps die G commute with the five elemental maps.…”
Section: Constructions and Definitionsmentioning
confidence: 97%
“…The first triangle, expressing the equality exp = die lin, is discussed in Yoshida [19] and Yalçın [18]. Let us review a few features that we shall be needing later.…”
Section: Constructions and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshida [27] later vindicated the prediction as to the "2-primary structure." Tornehave [24] and Yalçın [25] have shown that the 2-group case has rich special features. But, by the Odd Order Theorem, B(G) * captures nothing at all when |G| is odd.…”
Section: Unitsmentioning
confidence: 99%
“…Recently, E. Yalçin wrote a very nice paper ( [14]), in which he proves an induction theorem for B × for 2-groups, which says that if P is a 2-group, then any element of B × (P ) is a sum of elements obtained by inflation and tensor induction from sections (T, S) of P , such that T /S is trivial or dihedral.…”
Section: Introductionmentioning
confidence: 99%